2022
DOI: 10.3847/1538-4357/ac616d
|View full text |Cite
|
Sign up to set email alerts
|

Searching Far and Long. I. Pilot ALMA 2 mm Follow-up of Bright Dusty Galaxies as a Redshift Filter

Abstract: A complete census of dusty star-forming galaxies (DSFGs) at early epochs is necessary to constrain the obscured contribution to the cosmic star formation rate density (CSFRD); however, DSFGs beyond z ∼ 4 are both rare and hard to identify from photometric data alone due to degeneracies in submillimeter photometry with redshift. Here, we present a pilot study obtaining follow-up Atacama Large Millimeter Array (ALMA) 2 mm observations of a complete sample of 39 850 μm-bright dusty galaxies in the SSA22 field. Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 131 publications
(179 reference statements)
2
17
2
Order By: Relevance
“…However, determining the contributions of dusty galaxies at very high redshifts has been challenging. Here we focus on whether the 2 mm data find significant star formation at high redshifts (here z > 5), and we make comparisons with the 2 mm results of Zavala et al (2021) and Cooper et al (2022).…”
Section: Mm-based Redshift Estimatesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, determining the contributions of dusty galaxies at very high redshifts has been challenging. Here we focus on whether the 2 mm data find significant star formation at high redshifts (here z > 5), and we make comparisons with the 2 mm results of Zavala et al (2021) and Cooper et al (2022).…”
Section: Mm-based Redshift Estimatesmentioning
confidence: 99%
“…By comparison, the 850 μm flux drops with these higher redshifts. Then, through the use of the 2 mm-870 μm flux ratio, one can try to estimate redshifts for these galaxies (e.g., Casey et al 2021;Cooper et al 2022). However, as we discuss in this paper, redshifts are better estimated using the flux ratio of 2 mm to a shorter bandpass, such as 450 μm, where the gradient is steeper (see Figure 1(b)).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each source in the sample has at least two ALMA measurements by our selection criteria, but 44 (77%) have four or more ALMA measurements (two have three ALMA bands and the remaining 11 have just two ALMA bands). Thus, the FIR SEDs of our sample are generally better sampled than others in the literature (e.g., da Cunha et al 2021;Cooper et al 2022).…”
Section: Robust Subset Selectionmentioning
confidence: 87%
“…In one such study, da Cunha et al (2021) used an optically thin modified blackbody (MBB) and found a median β = 1.9 ± 0.4 for a sample of 27 DSFGs from the ALESS survey (Hodge et al 2013;Karim et al 2013) with ALMA 870 μm and 2 mm data. In another study, Cooper et al (2022) used a combined general opacity blackbody and power-law fit and found a median β = 2.4 ± 0.3 for a sample of 39 DSFGs in the SSA22 field (850 μm flux >5.55 mJy) with SCUBA-2 850 μm, AzTEC 1.1 mm, and ALMA 2 mm data.…”
Section: Introductionmentioning
confidence: 99%